2016
DOI: 10.1080/14397595.2016.1245176
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of paravertebral muscle atrophy and fatty degeneration in ankylosing spondylitis

Abstract: Chronic inflammation, cytokine-mediated fibrosis, immobilization, and postural changes in ankylosing spondylitis contribute to fatty degeneration and atrophy in the paravertebral muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 18 publications
6
28
0
Order By: Relevance
“…Another important finding from the same study was the significant fat degeneration at L3-4 levels in all patients with sacroiliitis. Similar results were shown by Resorlu et al [12].…”
Section: Discussionsupporting
confidence: 92%
“…Another important finding from the same study was the significant fat degeneration at L3-4 levels in all patients with sacroiliitis. Similar results were shown by Resorlu et al [12].…”
Section: Discussionsupporting
confidence: 92%
“…Although axSpa is a systemic disease, the initial inflammatory changes occur in the lumbo-pelvic region, and the lumbar paraspinal muscles are therefore a target for any primary or secondary pathological changes. Studies using MRI have demonstrated decreased CSA of the multifidus muscles, as well as changes in composition of the muscles (Akgul et al, 2013; Resorlu et al, 2017). Although exercise is beneficial in diseases such as axSpa, the mechanisms are not known.…”
Section: Changes In Trunk Muscles Associated With Low Back Pain and Smentioning
confidence: 99%
“…Paravertebral muscles, transversus abdominis, external oblique, internal oblique muscles forming the core have been shown to be active during endurance tests 22,23 . It is stated in some rheumatoid diseases that atrophy can be seen in these muscles and this atrophy may cause decrease in strength and endurance test scores 24 . However, we did not find any study examining the presence of atrophy in the trunk muscles or evaluating the trunk muscle morphology (ultrasound imaging), strength and endurance of SSc patients.…”
Section: Discussionmentioning
confidence: 99%